2022
DOI: 10.3390/electronics11142109
|View full text |Cite
|
Sign up to set email alerts
|

Technological Acceptance of Industry 4.0 by Students from Rural Areas

Abstract: In this study, our objective was to identify the factors that explain the acceptance of Industry 4.0 technologies by technical students. Industry 4.0 is made up of a series of technologies, such as the Internet of Things; cyber-physical systems; big data, data analytics, or data mining; cloud computing or the cloud; augmented reality or mixed reality; additive manufacturing or 3D printing; cybersecurity; collaborative robots; artificial intelligence; 3D simulation; digital twin or digital twin; drones. We desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 103 publications
(107 reference statements)
0
2
1
Order By: Relevance
“…This highlights the role of perceived value as a mediator between attitudes and adoption intentions, indicating that individuals' perceptions of the benefits and costs associated with adoption play a crucial role in forming intentions. The research results in contrast with previous studies by Cordero et al, [10], Castillo-Vergara et al, [56], Wang et al, [55], Toni et al [50], and Saeedi et al, [53], emphasize the variability in the weight of attitudes versus subjective norms in predicting intentions across different behaviors and individuals. Overall, the study underscores the importance of considering factors beyond attitudes in shaping adoption intentions and suggests tailored strategies to enhance the adoption of sustainable energy solutions.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This highlights the role of perceived value as a mediator between attitudes and adoption intentions, indicating that individuals' perceptions of the benefits and costs associated with adoption play a crucial role in forming intentions. The research results in contrast with previous studies by Cordero et al, [10], Castillo-Vergara et al, [56], Wang et al, [55], Toni et al [50], and Saeedi et al, [53], emphasize the variability in the weight of attitudes versus subjective norms in predicting intentions across different behaviors and individuals. Overall, the study underscores the importance of considering factors beyond attitudes in shaping adoption intentions and suggests tailored strategies to enhance the adoption of sustainable energy solutions.…”
Section: Discussioncontrasting
confidence: 99%
“…Cordero et al,[10] suggest that attitude influences the intention to adopt Industry 4.0 technology positively. Castillo-Vergara et al,[56] found that technological optimism positively affects the perception of technology's usefulness and ease of use. Toni et al,[50] and Saeedi et al,[57] also highlight the significant impact of attitude on the adoption of Industry 4.0 technology.…”
mentioning
confidence: 99%
“…Young population is familiar with industry 4.0 technologies (Cotet el al, 2020) and they will fully work using them in the future mining. Neverthelss, despite technological optimism positively influences perceived usefulness and ease of use of Industry 4.0 technologies by young trainee (Castillo-Vergara et al, 2022), it will be important to utilize older miners' knowledge for technology development and knowledge transfer to newer miners (Lund et al, 2024). 13 Currently subcontracted workers in Chile's mining industry has become an important social movement (Leiva and Campos, 2013;Hughes, 2016;Pérez, 2022).…”
Section: • Impact On the Overall Operationmentioning
confidence: 99%
“…These efforts aim to develop technological solutions and strategies to tackle the challenges unique to each particular context [9]. Research indicates that there is a need to adopt advanced technologies [10] [11], but the lack of adaptation generates a technological lag and the need for a digital transformation. Although specific problems may vary, the need to bridge the gap between the physical and digital worlds through the implementation of cyber-physical systems, DT, and Industry 4.0 technologies is a common theme [3] [12].…”
Section: Introductionmentioning
confidence: 99%